Reply to "Comments on Techniques and Architectures for Hazard-Free Semi-Parallel Decoding of LDPC Codes". (17th February 2010) - Rovini, Massimo; Gentile, Giuseppe; Rossi, Francesco; Fanucci, Luca
Abstract : This is a reply to the comments by Gunnam et al. "Comments on 'Techniques and architectures for hazard-free semi-parallel decoding of LDPC codes'", EURASIP Journal on Embedded Systems, vol. 2009, Article ID 704174 on our recent work "Techniques and architectures for hazard-free semi-parallel decoding of LDPC codes", EURASIP Journal on Embedded Systems, vol. 2009, Article ID 723465.